Pengaruh Berita Hoax Vaksin Covid-19 terhadap Sikap Masyarakat untuk Menerima Vaksin (Survei Pada Masyarakat di Kelurahan Jatinegara) - Purba, Martika Sella Br; Salman, Salman (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
Vaccine hoax news circulating on social media Facebook. The hoax news stated that it contained pork oil and microchips thus making people afraid to receive the vaccine. This study aims to determine whether or not there is an influence of the Covid-19 vaccine hoax news on people's behavior in Jatinegara Village. This research uses stimulus response theory. The research approach uses quantitative research with an explanatory type. Samples were taken as many as 150 respondents. The researcher concluded that there was an effect of the Covid-19 vaccine hoax news on people's attitudes to receiving vaccines in the Jatinegara village. Based on the data obtained from the calculation of the questionnaire, the hoax news variable shows that people are affected by hoax news. However, the percentage result of 21.3% can be said that the influence of hoax news is not large enough to influence people's attitudes.